2018
DOI: 10.1093/mnras/sty421
|View full text |Cite
|
Sign up to set email alerts
|

Ignition of detonation in accreted helium envelopes

Abstract: Sub-Chandrasekhar CO white dwarfs accreting helium have been considered as candidates for Type Ia supernova(SNIa) progenitors since the early 1980s (helium shell mass > 0.1M ). These models, once detonated did not fit the observed spectra and light curve of typical SNIa observations. New theoretical work examined detonations on much less massive (< 0.05M ) envelopes. They find stable detonations that lead to light curves, spectra and abundances that compare relatively well with the observational data. The exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…∆R was defined as 0.04 times the distance of the central detonating cell to the center of the white dwarf. This value leads to a detonation ignition in a volume similar to that found by Glasner et al (2018). This construction formally results in a symmetric detonation ignition volume around one point.…”
Section: Detonationsupporting
confidence: 66%
See 1 more Smart Citation
“…∆R was defined as 0.04 times the distance of the central detonating cell to the center of the white dwarf. This value leads to a detonation ignition in a volume similar to that found by Glasner et al (2018). This construction formally results in a symmetric detonation ignition volume around one point.…”
Section: Detonationsupporting
confidence: 66%
“…Radiative transfer calculations allow the discussion of their impact on the observables. Relating to question (1), Glasner et al (2018) investigated whether a helium detonation can ignite in the He shell. Röpke et al (2007) and Seitenzahl et al (2009) studied conditions for carbon detonation ignition and the processes leading to it were simulated by Fink et al (2007Fink et al ( , 2010 and Moll & Woosley (2013), addressing question (2).…”
Section: Introductionmentioning
confidence: 99%
“…The converging detonation waves trigger a second detonation at the carbon-oxygen core, hence producing a prompt eruption (Moll et al 2014;Raskin et al 2014;Tanikawa et al 2019;Gronow et al 2020). While some observational results seem to favor the double-degenerate scenario (Woosley & Kasen 2011;Maoz et al 2014;Glasner et al 2018), suggesting that they might constitute the majority population of thermonuclear supernovae (Flörs et al 2019;Cheng et al 2020;Li et al 2021), some recent studies found that they could be in a tight tension with the γ-ray ejected time against nickel-mass relation (Kushnir et al 2020).…”
Section: Appendix a Accuracy Of Linear Interpolationmentioning
confidence: 99%
“…The modeling of such processes is typically much longer than the hydrodynamics timescale in order to directly capture the first nuclear runaway from nuclear reactions. To resolve the first runaway, the simulation requires the hydrodynamics timescale t hyd to be smaller than the timescale of nuclear burning t burn and convection t conv , i.e., t hyd <t burn <t conv (Glasner et al 2018). Only recently have there been a few pioneering models using hydrodynamics simulations in the low Mach number regime to follow how the convection develops into nuclear runaway selfconsistently (Zingale et al 2013;Jacobs et al 2016).…”
Section: Connection To Work In the Literaturementioning
confidence: 99%